A review on the design criteria of biological aerated filter for COD, ammonia and manganese removal in drinking water treatment - Hassimi, Abu Hasan; Siti Rozaimah, Sheikh Abdullah; Siti Kartom, Kamarudin; Noorhisham Tan, Kofli (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/